2017
DOI: 10.1002/glia.23266
|View full text |Cite
|
Sign up to set email alerts
|

The function of contactin‐2/TAG‐1 in oligodendrocytes in health and demyelinating pathology

Abstract: The oligodendrocyte maturation process and the transition from the pre-myelinating to the myelinating state are extremely important during development and in pathology. In the present study, we have investigated the role of the cell adhesion molecule CNTN2/TAG-1 on oligodendrocyte proliferation, differentiation, myelination, and function during development and under pathological conditions. With the combination of in vivo, in vitro, ultrastructural, and electrophysiological methods, we have mapped the expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 71 publications
0
20
0
Order By: Relevance
“…However, stronger effects were demonstrated in the case of neural adhesive glycoproteins provided with key relevant regulatory roles in neural developmental control as is typically the case for Contactin family components [ 77 ] and in particular for Contactin 1 [ 55 , 78 ], for which a stronger downregulation, accounting to about 50% was demonstrated in the dorsal horn. This Contactin 1 behavior could be explained based on its cell type-specificity, which, besides the neuronal lineage, also concerns the glial, in particular the oligodendrocyte lineage in which it participates to the mechanism of myelination through its effects on nodal/paranodal regions organization [ 55 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, stronger effects were demonstrated in the case of neural adhesive glycoproteins provided with key relevant regulatory roles in neural developmental control as is typically the case for Contactin family components [ 77 ] and in particular for Contactin 1 [ 55 , 78 ], for which a stronger downregulation, accounting to about 50% was demonstrated in the dorsal horn. This Contactin 1 behavior could be explained based on its cell type-specificity, which, besides the neuronal lineage, also concerns the glial, in particular the oligodendrocyte lineage in which it participates to the mechanism of myelination through its effects on nodal/paranodal regions organization [ 55 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the adult rodent nervous system, there is knowledge of TAG-1 expression in the cerebellum, the mitral cells of the olfactory bulb, the hippocampus, and the juxtaparanodal domains of myelinated fibers (both at the axonal and glial membranes; Yoshihara et al, 1995; Wolfer et al, 1998; Traka et al, 2002). Considering the wider extent of detection of Tag-1 EGFP during the stages analyzed compared to the immunodetection with current antibodies, the transgenic strain in question is a valuable tool to further study the protein in the adult mouse (Bastakis et al, 2015; Zoupi et al, 2018). This could allow a variety of studies focusing on neurons, glia and potentially interneurons, as already seen in recent publications.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies on modulated V‐ATPase activity and TLR4 signaling in the context of de‐ and remyelination in vivo will be important to conduct and therefore deserve increased attention. Of note, a couple of recent studies identified other promising signaling pathways promoting (re)myelination in rodent models such as activated by teriflunomide (Göttle et al, ), the histamine receptor 3 modulator GSK247246 (Chen et al, ), the dual inhibitor VP3.15 (Medina‐Rodriguez et al, ), muscarinic receptor antagonists (Welliver et al, ) and contactin‐2/TAG‐1 (Zoupi et al, ). Although, these are attractive targets they have not yet advanced in terms of clinical assessment and application.…”
Section: Discussionmentioning
confidence: 99%